Spectra FTIR Analysis of Kedondong and Pumpkin Fruits, Sweet Potato and Carrot for Choosing Dye Sensitized Solar Cell (DSSC) Materials Using Multivariate Method - Maramba Meha, Engelia Rambu; Windarjoto, Windarjoto; Suyanto, Hery (BULETIN FISIKA; Vol 23 No 2 (2022): BULETIN FISIKA August EditionDO - 10.24843/BF.2022.v23.i02.p02, 2021)
Research has been carried out on the analysis of various kinds of fruit as an alternative material for Dye Sensitized Solar Cells (DSSC) using Fourier-Transform Infrared Spectroscopy  (FTIR) with the Multivariate method. This study used 6 fruits as samples with 2 fruits as validators (mangosteen and dragon fruits) and 4 other fruits as an alternative fruit (Kedondong fruit, sweet potato, pumpkin and carrot). The sample was made into powder and then was analyzed by FTIR. The FTIR spectra data were processed by the Multivariate method, especially the PCA and Clustering algorithm. The results show that both sweet potato and Kedondong fruit can be used as alternative materials for Dye Sensitized Solar Cell (DSSC) whose characteristics are closer to Dragon fruit.